The Concept of Ant in the Karachay-Balkar Ethnolinguoculture - Gelyaeva, Ariuka I.; Khuchinaeva, Jamilyat J.; Julietta B. Kumakhova, Julietta B. (The New Research of Tuva, 2026)
The article presents an interdisciplinary analysis of the concept of “Ant” in the Karachay-Balkar ethnolinguoculture. The methodological framework is based on a structured approach to the reconstruction and description of a cultural concept, which opens broad prospects for its examination in terms of form, idea, and regulatory function, and presupposes the integration of methods from various fields of knowledge and semiotic systems. The study draws on a representative corpus of verbal and non-verbal texts of the Karachay-Balkar ethnolinguoculture. Through the application of dictionary entries for the lexeme ant across different Turkic languages, it has been established that the representative of the concept, the word ant meaning “oath,” “sworn promise,” “vow,” or “pledge,” occurs in the vast majority of Turkic languages both as a noun and within analytical verbal constructions. The importance of the etymologization of the lexeme ant is emphasized, and several hypotheses regarding its origin are discussed. Attention is paid to the specificity of the lexeme “ant” as a performative utterance representing the unity of word and speech act performed at the moment of oath-taking. Examples are drawn from mythological texts, epic narratives, fairy tales, songs, paremias, rituals, as well as fragments of oaths of arbitration court members and everyday speech. These examples demonstrate the existence in the Karachay-Balkar ethnolinguoculture of various types of oaths that combine oath formulas with diverse semiotic means. It is established that the concept of ant is objectified within the Karachay-Balkar ethnolinguocultural space as a dynamic system, as evidenced by its various conceptual components associated with different chronological stages and reflecting the socio-cultural realities characteristic of each period.